2018
DOI: 10.1080/15384101.2018.1431596
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-targeting Salmonella typhimurium A1-R combined with recombinant methioninase and cisplatinum eradicates an osteosarcoma cisplatinum-resistant lung metastasis in a patient-derived orthotopic xenograft (PDOX) mouse model: decoy, trap and kill chemotherapy moves toward the clinic

Abstract: In the present study, a patient-derived orthotopic xenograft (PDOX) model of recurrent cisplatinum (CDDP)-resistant metastatic osteosarcoma was treated with Salmonella typhimurium A1-R (S. typhimurium A1-R), which decoys chemoresistant quiescent cancer cells to cycle, and recombinant methioninase (rMETase), which selectively traps cancer cells in late S/G, and chemotherapy. The PDOX models were randomized into the following groups 14 days after implantation: G1, control without treatment; G2, CDDP (6 mg/kg, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 77 publications
2
58
0
Order By: Relevance
“…Previously, we demonstrated that S. typhimurium A1-R inhibits growth of primary and metastatic tumors as a monotherapy in PDOX models of many types of malignant tumors [12, 17, 19, 20]. S. typhimurium A1-R can destroy tumor blood vessels and enhance CD8 + T-cell infiltration into the tumors as well [32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that S. typhimurium A1-R inhibits growth of primary and metastatic tumors as a monotherapy in PDOX models of many types of malignant tumors [12, 17, 19, 20]. S. typhimurium A1-R can destroy tumor blood vessels and enhance CD8 + T-cell infiltration into the tumors as well [32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…S. typhimurium A1-R can directly target and kill cancer cells [49] as well as decoy the cancer cells from the chemoresistant G 0 /G 1 phase to the chemosensitive S-phase of the cell cycle, making them more susceptible to GEM [50][51][52]. A similar type of cell-cycle decoy occurred when cancer cells were injected with an adenovirus [53].…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has developed clinically-relevant mouse models of cancer for discovery of transformative therapy for pancreatic cancer, the patientderived orthotopic xenograft (PDOX) nude mouse model, with the technique of surgical orthotopic implantation (SOI). These models include breast [5], ovarian [6], lung [7], cervical [8], colon [9][10][11], and stomach cancer [12], as well as sarcoma [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and melanoma [31][32][33][34][35][36][37][38] and pancreatic cancer [33,[39][40][41][42]. The PDOX model, developed by our laboratory over the past 30 years, has many advantages over subcutaneous-transplant models which grow ectopically under the skin and rarely metastasize [43].…”
Section: Introductionmentioning
confidence: 99%
“…However, its therapeutic potential as an anti-cancer agent remain unexplored. Among more than 2500 NTS serovars, S. Typhimurium VNP20009 [2][3][4], an auxotrophic mutant strain of S. Typhimurium A1-R [5,6], has been successfully studied and was even tested in phase I clinical trial for the treatment of solid tumors [7]. Many features of Salmonella namely the ability to thrive in hypoxic environment of the tumor, to induce innate immune response against tumor or its bactofection, and ability to release anticancer genes within tumor were found to be favorable for tumor regression in animal models [8][9][10].…”
Section: Introductionmentioning
confidence: 99%